Upaya Diversi terhadap Anak yang Berkonflik dengan Hukum di Kepolisian Resort Jakarta Selatan - Halimatu Sa'diah Palupi; Nadia Utami Larasati (Anomie, 2019)
This research discusses the children who are conflicted with the law or the perpetrator’s child. Psychologically, the child who committed a criminal act is still labile and can not responsibility to what he has done. Incorporating a child into a prison environment is the last solution. Another effect that occurs when the child enters the jail is a labelling as a convict committed by the public against a criminal offense. There are now regulations governing the children criminal justice system, LAW No 11 year 2012, in which there is an diversion. The data collection techniques used in this study were interviews. The concept of restorative justice defines that criminal settlement involves perpetrators, victims, families of victims/perpetrators, and other related parties to jointly seek a fair settlement by emphasizing recovery on the state of And not retaliation. The implementation of the diversion provides protection against children in order not to be in direct contact with formal criminal justice, it is the main principle of restorative justice and diversion.